Genetic diagnosis of familial hypercholesterolaemia: the importance of functional analysis of potential splice-site mutations. Issue 5 (1st May 2009) - Bourbon, M; Duarte, M A; Alves, A C; Medeiros, A M; Marques, L; Soutar, A K
Abstract : Familial hypercholesterolemia (FH) results from defective low-density lipoprotein receptor (LDLR) activity, mainly due to LDLR gene defects. Of the many different LDLR mutations found in patients with FH, about 6% of single base substitutions are located near or within introns, and are predicted to result in exon skipping, retention of an intron, or activation of cryptic sites during mRNA splicing. This paper reports on the Portuguese FH Study, which found 10 such mutations, 6 of them novel. For the mutations that have not been described before or those whose effect on function have not been analysed, their effect on splicing was investigated, using reverse transcriptase PCR analysis of LDLR mRNA from freshly isolated blood mononuclear cells. Two of these variants (c.313+6 T→C, c.2389G→T (p.V776L)) caused exon skipping, and one caused retention of an intron (c.1359−5C→G), whereas two others (c.2140+5 G→A and c.1061−8T→C) had no apparent effect. Any effect of c.1185G→C (p.V374V) on splicing could not be determined because it was on an allele with a promoter mutation (−42C→G) that was probably not transcribed. Variants in four patients lost to follow-up could not be tested experimentally, but they almost certainly affect splicing because they disrupt the invariant AG or GT in acceptor (c.818−2A→G) or donor (c.1060+1G→A, c.1845+1delG and c.2547+1G→A) spice sites. These findings emphasise that care must be taken before reporting the presence or absence of a splice-site mutation in the LDLR gene for diagnostic purposes. The study also shows that relatively simple, quick and inexpensive RNA assays can evaluate putative splicing mutations that are not always predictable by available software, thereby reducing genetic misdiagnosis of patients with FH.